Gut microbiota and fecal metabolic signatures in rat models of disuse-induced osteoporosis - Qiao, Xiaochen; Zhang, Kun; Li, Xiaoyan; Lv, Zhi; Wei, Wenhao; Zhou, Ruhao; Yan, Lei; Pan, Yongchun; Yang, Sen; Sun, Xiaojuan; Li, Pengcui; Xu, Chaojian; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Assessing the correlation between gut microbiota (GM) and bone homeostasis has garnered increasing research interest. Consequently, GM dysbiosis has been found to be closely related to abnormal bone metabolism. However, the role of GM in disuse-induced osteoporosis (DIO), remains poorly understood. In the current study, we analyzed the signatures of GM and fecal metabolomics to explore their potential correlations with DIO pathogenesis. Methods: DIO rat models and controls (CON) underwent micro-CT, histological analyses, and three-point bending tests; subsequently, bone microstructures and strength were observed. ELISAs were used to measure the biochemical markers of bone turnover while GM abundance was observed using 16S rDNA sequencing. Metabolomic analyses were used to analyze alterations fecal metabolites. The potential correlations between GM, metabolites, and bone loss were then assessed. Results: In the DIO group, the GM abundance and composition of the metabolites were significantly altered compared to those in the CON group. Moreover, DIO significantly altered fecal metabolites. More specifically, an abnormally active pathway associated with bile acid metabolism, as well as bacteria related to bone/tissue volume, were identified. Lithocholic acid, which is the main secondary bile acid produced by intestinal bacteria, was then found to have a strong relationship with Erysipelatoclostridium, Proteus, Akkermansia, and Roseburia. Alterations in the intestinal flora and metabolites in feces therefore contribute to DIO-induced bone loss. Indeed, GM and fecal metabolites are closely correlated in DIO. Conclusions: Changes in GM abundance and function induced by DIO may represent key factors affecting bone homeostasis. These ﬁndings provide new insights into the pathogenesis of DIO.